Incorporación de un artículo en el capítulo II del título V, del libro segundo del código de la niñez y adolescencia, sobre mediación como método obligatorio, previa a la judicialización de las demandas de alimentos bajo el principio de economía y celeridad procesal - Ludeña Carrillo, Vanessa Natalia (2014)
This research is funded through a methodology based on the internal regulations of the National University of Loja, a detailed study has been carried into practice to meet the approval of the thesis report, the results presented in the interpretation and analysis of implementation of surveys and interviews with due discussion include the verification of objectives, the test of the hypothesis and the legal and doctrinal criteria opinion, underpinning Reform Proposal; order to present the conclusions and recommendations of the final report of this thesis. This project is aimed at implementing legislation on mandatory mediation prior to the prosecution of the demands for food, because the content of this research is based on a searing social reality, whose protagonists are unfortunately children and adolescents , since they have experienced the slow clearance process, when appearing before the courts to claim their right to food; since due to the large number of processes that this matter is heard in the judicial units of childhood family and adolescence, there is no efficiency to meet promptly all claims submitted by users, so that justifies the implement reform based on mandatory mediation prior to the prosecution of the demand for food to be presented later, the first beneficiary will be the child or adolescent. Because mediation helps access to justice and the effectiveness of it, eliminating the thought that a conflict is similar to a trial, this rule of judgment is unreasonable in any community. Perhaps in many conflicts requires going to court to be resolved, when not transigible matter, but in regard to the remaining caseload in the justice system, may mediate such as food since they are transigible matter. It could be possible that the issue through mediation of the caseload of the judiciary is resolved, courts descongestionaría consequently would work better. Set the tone that brokered a balance of power exists for both parties. Mediation and courts of justice system would complement each other and work well if the mediation, the courts also because they have mediation to resolve the problems and vice versa. It has created a culture of real dialogue, defeating the litigious culture and overcrowding of courts, many of the processes are very expensive for the state and citizens. Mediation helps to decongestion and the transformation of the justice system, helps the ordinary justice system by balancing but mostly helps the parties to properly live in a culture of dialogue and peace.